1994
DOI: 10.1080/02772249409358047
|View full text |Cite
|
Sign up to set email alerts
|

Leaching processes of the dicalcium silicate and copper oxide solidification/stabilization system

Abstract: Cement based solidification/stabilization technology has been widely practiced for the treatment of inorganic hazardous wastes, especially metal-bearing wastes. The advantage of using the solidification/stabilization process is that the mobility of the hazardous materials is greatly retarded in the final disposal sites. The purpose of this study is to assess the stability of a synthetic solid waste through the renewable leaching test. A major cement constituent, dicalcium silicate (C 2 S), was used as a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Previous studies [ 33 , 34 , 35 ] have found that heavy metals will combine with OH− or silicate and solidify in calcium salt when mixed with cement-based materials, and they can also be adsorbed in C-S-H gel to enter the crystal structure. Pb can usually be adsorbed on the surface of hydration products.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [ 33 , 34 , 35 ] have found that heavy metals will combine with OH− or silicate and solidify in calcium salt when mixed with cement-based materials, and they can also be adsorbed in C-S-H gel to enter the crystal structure. Pb can usually be adsorbed on the surface of hydration products.…”
Section: Resultsmentioning
confidence: 99%